Perancangan dan Analisis Konstruksi Mekanik pada Robot Pemadam Api Hexapod Menggunakan Metode Finite Element Analysis dan Inverse Kinematics - Oscar Haris; Taufik Rahman (Jurnal Rekayasa Mesin, 2023)
Fires often occur in dense urban areas, judging from their geographical location, urban areas that have dense populations which are areas prone to fire disasters which result in very difficult handling because the location is difficult to reach by fire engines. One of the countermeasures that can be done is by using a hexapod robot. In this research, the steps taken are by designing the mechanical construction of the robot using Autodesk Inventor Software and performing FEA analysis using Autodesk Inventor Stress Analysis Software, after that perform calculations and simulations of Inverse kinematic using RoboAnalyzer Software. The results obtained in this study are the dimensions of the hexapod SAR robot which is designed to have a total length of 145 cm, width 85 cm and height 85 cm, with a robot weight of 42.5 kg with a water tank capacity of 44.32 liters. The grip on the robot has a multifunctional type with a maximum load that can be lifted is 50 kg. The results of the inverse kinematic angle that can be used on the robot are coxa angle 0°, femur 45° and tibia -135°. In the FEA simulation, the largest von misess stress is 144.2 mpa and the largest safety factor value is 1.73 ul in the safe category. With the results of this study, it can be concluded that the robot can easily go in and out of the room during evacuation and has a safe construction design equipped with a strong grip in lifting loads and a flexible and efficient water sprayer.